DISCOVERY: prevalence of transthyretin (TTR) mutations in a US-centric patient population suspected of having cardiac amyloidosis. (1st October 2020) - Akinboboye, Ola; Shah, Keyur; Warner, Alberta L.; Damy, Thibaud; Taylor, Herman A.; Gollob, Jared; Powell, Christine; Karsten, Verena; Vest, John; Maurer, Mathew S.
Abstract: Background: Hereditary transthyretin-mediated amyloidosis (hATTR amyloidosis) is a multisystem disease that presents with polyneuropathy and/or cardiomyopathy. Methods: DISCOVERY, a multicenter screening study, enrolled patients with clinically suspected cardiac amyloidosis to determine the frequency of transthyretin ( TTR ) mutations and assess disease characteristics. Results: Of 1007 patients, the majority were from the US (84%), Black/African American (56%), male (63%), and with a mean (standard deviation) age of 65 (13) years. Among 1001 patients with genotyping results, 74 (7%) had a pathogenic TTR mutation (71/836 [8%] from the US). Val122Ile was the most common mutation, found in 11% of Black/African American patients overall; Black/African American ethnicity was an independent predictor of having a pathogenic TTR mutation. Additional independent predictors of such mutations in the total population and Black/African American group were interventricular septum thickness, low electrocardiogram voltage, and age. Conclusions: Pathogenic TTR mutations occurred in 8% of US patients with suspected cardiac amyloidosis. Most mutations were Val122Ile, almost exclusively found in Black/African American patients. Disease often remains undetected until advanced and difficult to treat, therefore, clinicians should assess at-risk patients for hATTR amyloidosis as early as possible.